Using active tuned mass dampers with constrained stroke to simultaneously control vibrations in wind turbine blades and tower. Issue 7 (May 2019) - Cong, Cong
Simultaneous control of wind turbine blades and tower vibrations is studied in this article. Four active tuned mass dampers have been incorporated into each blade and tower to reduce vibrations. A decentralized constrained H ∞ velocity output feedback which restricts the tuned mass damper stroke as a hard constraint is proposed by solving linear matrix inequality. Each active tuned mass damper is driven individually by the output of the corresponding velocity signal. Considering the structural dynamics subjected to gravity, variable rotor speed, and aerodynamic loadings, a model describing dynamics of rotating blades coupled with tower, including the dynamics of active tuned mass dampers, was developed by Euler–Lagrangian formulation. A numerical simulation is carried out to verify the effectiveness of the proposed decentralized control scheme. Investigations show promising results for the active tuned mass damper in simultaneous control blade vibrations and tower vibrations by decentralized control approach. Numerical results demonstrate that the decentralized control has the similar performance compared to centralized control and effectively reduce the displacement of vibrations.